Nanomolar Potency and Metabolically Stable Inhibitors of Kidney Urea Transporter UT-B - Anderson, Marc O. (2012)
Urea transporters, which include UT-B in kidney microvessels, are potential targets for development of drugs with a novel diuretic (‘urearetic’) mechanism. We recently identified, by high-throughput screening, a triazolothienopyrimidine UT-B inhibitor, 1, that selectively and reversibly inhibited urea transport with IC(50) = 25.1 nM and reduced urinary concentration in mice (Yao et al. J. Am. Soc. Nephrol., in press). Here, we analyzed 273 commercially available analogues of 1 to establish a structure–activity series and synthesized a targeted library of 11 analogues to identify potent, metabolically stable UT-B inhibitors. The best compound, {3-[4-(1,1-difluoroethyl)benzenesulfonyl]thieno[2,3-e][1,2,3]triazolo[1,5-a]pyrimidin-5-yl}thiophen-2-ylmethylamine, 3k, had IC(50) of 23 and 15 nM for inhibition of urea transport by mouse and human UT-B, respectively, and ~40-fold improved in vitro metabolic stability compared to 1. In mice, 3k accumulated in kidney and urine and reduced maximum urinary concentration. Triazolothienopyrimidines may be useful for therapy of diuretic-refractory edema in heart and liver failure. [Image: see text]